Alternative coiled coil electrostatic interfaces from side chain length variance - Ryan, Shannon John, author; Kennan, Alan, advisor; Williams, Robert M., committee member; Rappé, Anthony K., committee member; Elliott, C. Michael, committee member; Woody, Robert W., committee member (Colorado State University. Libraries, 2006)
The alpha helical coiled coil is a ubiquitous structural element found throughout nature and is comprised of two or more α-helical strands bundled via a left handed superhelical twist. These structures are attractive scaffolds for molecular recognition studies due to their regular primary sequence heptad repeat denoted abcdefg. The folding of component strands is primarily directed by hydrophobic interactions between residues at positions a and d. In addition, residues at positions e and g comprise the hydrophilic interface and can confer additional specificity, generally via electrostatic interactions. Hydrophilic contacts have been shown to contribute to orientation and oligomerization specificity, primarily through the minimization of Coulombic repulsion. We sought to investigate the role of sidechain length and functionality on homodimer and heterodimer specificity. In particular, chain length variants of glutamic acid and lysine with one to four methylenes were desired. The lysine analogs were commercially available and the glutamic acid variants were synthesized utilizing an olefin cross metathesis strategy between a bis-protected allyl glycine and Grubbs' first and second generation ruthenium catalysts. This modular approach allows access to different amino acid analogs by choice of metathesis partners as well as choice of protecting group. Solid phase peptide synthesis can proceed utilizing alpha amino acids protected with a Boc or Fmoc group. Initial attempts using a Boc strategy were unsuccessful and discarded in favor of an Fmoc one. These amino acids were incorporated into a sequence based on the coiled coil domain of GCN4 with persubstitution of e and g positions with the appropriate carboxylic acid or amine residues. Pure component solutions bearing chain length extended carboxylate side chains contain a helical signal as measured by circular dichroism (CD) spectroscopy, while corresponding amines do not. Equimolar heterodimeric complexes contain a range of stabilities as measured by CD. These stability differences can be exploited to control complex formation. Most notably, the native glutamic acid - lysine interaction can be exchanged to form the more stable side chain length extended carboxylate - lysine complex.
Keywords: organic chemistry; biophysics